Studying the Possibility of Application ir Spectroscopy for Raw Material Identification Valeriana wolgensis Kazak. and Valeriana dudia L. - O. A. Kolosova; O. V. Trineeva (Разработка и регистрация лекарственных средств)
Introduction. Recently, IR spectroscopy has been increasingly used to identify various groups of biologically active substances (BAS) in plant objects. It is known that plants are capable of accumulating various BAS. Currently, there is no reliable, complete and accessible database of IR spectra of medicinal plant raw materials (MPR), which has a multicomponent composition, which is necessary for solving specific practical problems. It is of interest to use express methods of non-destructive testing for the purpose of identifying medicinal plant raw materials, as well as differential diagnostics of closely related species and various varieties of medicinal plants, which allow the analysis of raw materials in the shortest possible time, while maintaining the possibility of further vegetation. These types of difficult to distinguish raw materials include 9–14 (according to various sources) closely related plant species of the genus Valeriana, included, according to the accepted classification of V. I. Grubov with additions and changes by V. N. Voroshilov in the collection cycle (V. officinalis L.) of the Officinales Grub. series, and are characterized by an extremely similar composition of the metabolome.Aim. The purpose of this study was to study the possibility of using IR spectroscopy for the identification of MPR of Valeriana wolgensis Kazak. and Valeriana dudia L.Materials and methods. The objects of the study were rhizomes with roots, grass of Valeriana wolgensis Kazak. and Valeriana dudia L. Samples were col-lected in the Voronezh region in 2019 on the banks of the Ikorets river in the village of Sredny Ikorets, Liskinsky district and in the vicinity of the village of Belogorye, Podgorensky district. IR spectra were obtained without preliminary sample preparation on a IR Fourier spectrometer VERTEX 70 (Bruker, Germany) by the disturbed total internal reflection method and subsequent pro-cessing with the OMNIC or GRAMS 4/32 program.Results and discussion. In all spectra of the studied samples, absorption bands reflecting the general chemical composition were found. Similar absorption bands were observed, differing only in intensity. The spectra of similar groups of raw materials (herbs and rhizomes with roots) of the studied species of Valeriana were especially close to each other. In the IR spectra of the powders of the medicinal product under study, one can distinguish absorption bands characteristic of the hydroxyl groups of the cyclopentanepyrane skeleton of valepotriates: 3296–3280 cm-1. The complex absorption band in the region of 2958–2844 cm-1 is due to stretching vibrations of numerous methyl and methylene groups. Bending vibrations of the same groups give characteristic peaks at 1751–1407 cm-1 and about 700 cm-1 (790–720 cm-1 – pendulum vibrations of methylene groups). At the same time, among the main BAS of this medicinal product, the dominant compounds are those in which the methylene groups are closed in unstressed rings, which is manifested in bands in the range of 1420–1400 cm-1. The absorption bands in the range of 3296–3280 cm-1 in the IR spectra of the medicinal product of the studied species are due to stretching vibrations of the hydroxyl group in intermolecular hydrogen bonds. Based on the data obtained, the thermodynamic characteristics of the identified bonds, such as energy (EH) and length (R), were calculated. Valepotriates containing a cyclopentanepyran skeleton with five hydroxyl groups – polyhydrooxycyclo-pentanepyrane, in the studied medicinal plant, according to IR data, polyassociates are formed with characteristic absorption frequencies at 3400–3200 cm-1. The specific frequencies identified in the spectrum can be considered characteristic for a certain type of raw material of Valeriana and can be used as markers in determining the authenticity and species by the IRS method.Conclusion. The studies have shown that the IR Fourier spectroscopy of the disturbed total internal reflection can be used to obtain individual IR spectra of MPR of various morphological groups. The data obtained, in general, indicate the similarity of the chemical composition of two closely related species of valerian harvested in the Voronezh region, which, in addition to other studies of the metabolome composition, justifies the possibility of their use along with the official raw material of Valeriana officinalis L. The formation of hydrogen bonds and their character between BAS molecules in the studied medicinal product was established by IR spectroscopy. The results obtained indicate that the method used is promising for the rapid assessment of the medicinal product authenticity.